MENINGKATKAN KEMAMPUAN MENGGAMBAR KONSTRUKSI DENGAN MENGGUNAKAN SOFTWARE AUTOCAD: STUDI TENTANG EFEKTIVITAS MEDIA PEMBELAJARAN - Adela Tri Lestari (CV. ADIBA AISHA AMIRA, 2025)
Vocational high school students require several skills that will be utilized when they complete their studies in school. One of the desired skills is the ability to draw construction using the AutoCAD program. The ultimate skill expected from students is the capability to create construction drawings in the form of 2-D models. The primary focus of this research is to determine the extent to which AutoCAD can serve as an eflective learning tool in developing the construction drawing competence of vocational high school students. This study holds practical implications for teachers and educational institutions in vocational high schools by emphasizing the importance of integrating technology such as AutoCAD into the curriculum to prepare students with relevant and necessary skills for the construction industry. Consequently, the findings of this research can provide concrete guidance for the development of more eflective learning strategies at the vocational high school level.